Analisis Kinerja Keuangan Perusahaan dengan Analisis Du Pont Pada Perusahaan PT. Phapros Tbk. Tahun 2018-2023 - Putri Kemala Dewi Lubis; Deyren Firmansyah; Elsa Aurel Agustine Situmorang; LumbanBatu, Selfiana (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study aims to analyze the financial performance of PT. Phapros Tbk during the 2018-2023 period using the DuPont model. Return on Investment (ROI), and Return on Equity (ROE) as tools to evalute a company”s efficiency and profitabilityThe analysis results indicate that PT. Phapros Tbk's financial performance has declined over the past six years. The average NPM was recorded at 6.195%, significantly below the industry standard of 20%, indicating challenges in generating profit from sales. The average TATO of 0.56 times also suggests that asset utilization efficiency remains lower than the industry standard of 2 times. ROI experienced a significant decline, with an average of 3.37%, reflecting the company's low return on investment. Additionally, ROE showed a downward trend, averaging 8.27%, dropping from 19.73% in 2018 to only 1.35% in 2023. This decline was influenced by various factors, including rising production costs, industry competition, and unfavorable economic conditions. Therefore, the company needs to enhance operational efficiency, optimize asset utilization, and implement more innovative business strategies to improve profitability and competitiveness in the pharmaceutical industry.